2009
DOI: 10.1007/s11160-009-9116-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of invasive fish species in a river transposition region: evolutionary chromosome studies in the genus Hoplias (Characiformes, Erythrinidae)

Abstract: Karyotypic analyses were performed in fishes from the genus Hoplias (H. malabaricus and H. lacerdae groups) from the São Francisco River basin (Brazil), in an impacted region by a river transposition which altered the local ecology and fish fauna. The karyotypes were investigated using chromosomal markers obtained from classic and molecular cytogenetics (Giemsa, CMA 3 and DAPI staining, C-banding, Ag-NORs, and FISH with 18S rDNA, 5S rDNA and 5SHindIII satellite DNA probes). Two karyotypic forms were found for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
(31 reference statements)
3
35
0
2
Order By: Relevance
“…Although this proximal 5S rDNA site has not been observed in the majority of populations of H. malabaricus analyzed thus far, it is likely to be a plesiomorphic condition, once this similar character state has been observed in other species of the genus Hoplias, such as H. intermedius (cited as H. aff. lacerdae) and in some karyomorphs/populations of H. malabaricus (Ferreira et al, 2007;Blanco et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although this proximal 5S rDNA site has not been observed in the majority of populations of H. malabaricus analyzed thus far, it is likely to be a plesiomorphic condition, once this similar character state has been observed in other species of the genus Hoplias, such as H. intermedius (cited as H. aff. lacerdae) and in some karyomorphs/populations of H. malabaricus (Ferreira et al, 2007;Blanco et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a certain degree of intra-karyomorph variation would be expected, considering that the H. malabaricus complex is widely distributed in the river basins of South America and is known to contain high levels of karyotype polymorphism. Indeed, Blanco et al (2010) recently reported extensive karyotypic variation in karyomorph A.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been studied intensively using a cytogenetic approach, which revealed a karyotypic polymorphism among populations from distinct river basins (Bertollo et al, 2000;Rosa et al, 2009;Santos et al, 2009;Blanco et al, 2010). Seven karyomorphs (denominated A-G) have been identified based on diploid number and chromosome morphology, and are currently recognized as distinct independent evolutionary units (Bertollo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A similar well-recorded case occurred when the Piumhi River (with its 22 tributaries) which belonged to the Upper Paraná River basin was entirely transferred to São Francisco River basin after construction of the Furnas hydroelectric power dam [54]. This transposition introduced at list nine species from Upper Paraná River basin to São Francisco River basin [55,56,57,58,59]. However, in general, the impact of transpositions of rivers due to hydroelectric power dams are rarely recorded.…”
Section: Discussionmentioning
confidence: 80%